DESIGN AND FINITE ELEMENT ANALYSIS FOR MOVING SYSTEM STRUCTURE OF NC FORMING MACHINE - LIU LiMin; LIU BoQing; LIU Feng; DONG XiaoLi (Jixie qiangdu)
The moving system is the most critical part of numerical control（ NC for short） forming machine to achieve its fundamental function,but also the most importent part that affect the processing accuracy. The moving system of forming machine were lightweight designed firstly. Based on lightweight design principles,aluminum material was adopted on its key components of Y and Z axis,and the sandwich structure which has advantages of lightweight core and large inertia moment. Then structural static analysis and mode analysis of moving system were done by using the method of FEM numerical simulation,and the engineering verification was carried out. Results of the study show that the strength and stiffness of the moving system can satisfy the use requirement and allowable conditions of the forming machine.